Disturbance rejection control solution for ship steering system with uncertain time delay. (1st February 2015) - Lei, Zhengling; Guo, Chen
Abstract: The control problem for a ship steering system with uncertain time delays is discussed in this paper. The system uncertainties, including parameters and delay variations as well as unmodeled dynamics, are taken as "internal disturbances", while ocean movements are taken as "external disturbances". The combination of the two is considered as the "total disturbances" of the system. With the aid of a modified Smith predictor, an extended state observer (ESO) is constructed to estimate the total disturbances. By compensating its effects in a closed loop, the system is reduced to a set of cascaded integrators, which can be easily handled. The advantages of the proposed approach lie in two aspects: (1) it does not need an accurate model of the system; (2) it is robust against delay variations. The simulation results validate the strong disturbance rejection capability of the proposed method. Abstract : Highlights: An ADRC-based cascaded integrators predictor scheme was proposed for ship steering system with uncertain time delay. Assume the system time delay was too large to keep the frequency stability of the closed loop system in simulation study. The simulation results show that the proposed method is robust against delay variations and parameter perturbations.